The divine and the problem of violence - Wali, Wafaa Esmat (AUC Knowledge Fountain, 2018)
In 1961, Emmanuel Levinas published his seminal work Totality and Infinity: An Essay on Exteriority1 in which he proposed his theory: ethics as First philosophy. Levinas proposes that an ethical relationship with an "infinitely other", a relationship that is based on a face-to-face encounter is what can save humanity from violence. In 1967, Jacques Derrida published an essay, "Violence and Metaphysics"2, in which he responded to Levinas and criticized him for committing "violence" towards Greek logos. According to Derrida, Levinas's philosophy is in contradiction with the premises of Greek philosophy and language. This paper examines both texts and further explores the question of violence.